Factors influencing readiness for artificial intelligence: a systematic literature review - Wajid Ali; Abdul Zahid Khan (Data Science and Management)
Public-and private-sector organizations have adopted artificial intelligence (AI) to meet the challenges of the Fourth Industrial Revolution. The successful implementation of AI is a challenging task, and previous research has advocated the need to explore key readiness before AI implementation. The objective of this study is to identify the AI readiness factors explored by different authors in past research. To achieve this, we conducted a rigorous literature review. The approach used in the systematic literature review is also discussed. A rigorous review of 52 studies from various journals and databases (Science Direct, Springer Link, Institute of Electrical and Electronics Engineers, Emerald, and Google Scholar) identified 23 AI readiness factors. The key factors identified were mainly related to organizational information technology infrastructure, top management support, resource availability, collaborative culture, organizational size, organizational capability, compatibility, data quality, and financial budget, whereas the other 15 were potential factors in AI readiness. All of these factors should be considered before the implementation of AI in any organization. The findings also reflect a high failure rate, including AI readiness factors, which are intended to facilitate AI adoption in organizations and reduce the frequency of failures. These factors will aid management in developing an effective strategy for AI implementation in organizations.